SOCIAL RESEARCH METHODS IN FEMINIST'S PERSPECTIVE: A NEW WAY IN DOING SOCIOLINGUISTIC QUALITATIVE RESEARCH - Kuntjara, Esther (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Traditional research methods have been dominated by positivism which assumes the importance of objectivity, contextual independency, linear causality and value free research. Feminist researchers found that such methods do not suit their inquisitive needs especially in the study of women. Naturalistic research methods, however, do not only suit them but they are also able to voice women's problems. Two methods, i.e. interviewing and ethnography are discussed as to how they are commonly used by feminist researchers on many social studies on women, including the linguistic studies of gender.